Coach terminal as important element of transport infrastructure - Gromule, Vaira; Yatskiv, Irina (Transport, 2007)
The determination of the coach terminal as passenger logistics hub is described. The factors responsible for successful functioning of this hub are discussed. The location of the coach terminal is one of the important factors. The present coach terminal is located in the heart of the city where land availability is critical. The simulation model of the terminal was developed to complement the design and construction of a new one. The used simulation package VISSIM has visual reference to assist in explaining the complexity of transport node's job and analysis of possible congestions. During the development of the modelling the critical bottlenecks are identified and decisions are taken to reduce the risk of their occurrence, the solution being immediately incorporated into the final design of the coach terminal under development.First Published Online: 27 Oct 2010